2021
DOI: 10.3389/fimmu.2021.749708
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Immunity: Underappreciated Functions of Intestinal Macrophages

Abstract: The gastrointestinal tract hosts the largest compartment of macrophages in the body, where they serve as mediators of host defense and immunity. Seeded in the complex tissue-environment of the gut, an array of both hematopoietic and non-hematopoietic cells forms their immediate neighborhood. Emerging data demonstrate that the functional diversity of intestinal macrophages reaches beyond classical immunity and includes underappreciated non-immune functions. In this review, we discuss recent advances in research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 230 publications
(399 reference statements)
1
17
0
1
Order By: Relevance
“…This suggests that SI eosinophils promote the maturation or survival of mature intestinal macrophages following microbial colonization. Mature intestinal macrophages regulate the intestinal barrier (Chiaranunt et al, 2021;Muller et al, 2014). In line with this, we observed that although GF Ddbl.GATA1 and BALB/c mice did not exhibit differences in permeability or intestinal transit time (Figures 6F and 6G), microbial colonization resulted in increased permeability and transit time in the absence of eosinophils (Figures 6F and 6G).…”
Section: Microbial Colonization Drives Homeostatic Si Eosinophil Func...supporting
confidence: 85%
See 1 more Smart Citation
“…This suggests that SI eosinophils promote the maturation or survival of mature intestinal macrophages following microbial colonization. Mature intestinal macrophages regulate the intestinal barrier (Chiaranunt et al, 2021;Muller et al, 2014). In line with this, we observed that although GF Ddbl.GATA1 and BALB/c mice did not exhibit differences in permeability or intestinal transit time (Figures 6F and 6G), microbial colonization resulted in increased permeability and transit time in the absence of eosinophils (Figures 6F and 6G).…”
Section: Microbial Colonization Drives Homeostatic Si Eosinophil Func...supporting
confidence: 85%
“…Intestinal macrophages maintain homeostasis and dampen inflammation in the intestine, regulate intestinal permeability, and support neuronal homeostasis (Bain and Schridde, 2018;Chiaranunt et al, 2021), and their turnover and functional diversification is known to be driven by the microbiota (Chen et al, 2022;Kang et al, 2020). Our data show that eosinophils promote the ''monocyte waterfall'' pathway maturation of newly recruited bone-marrow-derived monocytes within the SI environment following colonization.…”
Section: Discussionmentioning
confidence: 77%
“…Food interacts with our innate immune system primarily through the gastro-intestinal tract and the microbiome. Macrophages line the intestinal tract (Chiaranunt et al, 2021). A healthy diet and a normal body mass index (BMI) are known to foster a healthy microbiome and anti-inflammatory bacteria (Sohail et al, 2019;Chen et al, 2021).…”
Section: Lifestyle and The Immune Systemmentioning
confidence: 99%
“…Although abundant in the colorectal mucosa, CX3CR1 + MNPs have been mostly overlooked in studies on HIV-1 transmission. Moreover, the composition and function of the intestinal MNP subset is still a subject of debate ( Chiaranunt et al., 2021 ) and needs to be clarified in the context of mucosal HIV/SIV infection.…”
Section: Introductionmentioning
confidence: 99%